Factors affecting depression among higher secondary level students of Biratnagar, Nepal. - Khatiwada Upadhaya,Shikha (2014)
ABSTRACT: Background :Mental health is one of the priority program of Nepal government in NSHP-IPII and depression is one of the mental health illness which is 4th leading cause of morbidity in mental hospital of Nepal.(Nepal, 2068/69) Depression affects more than 350 million people worldwide and affects individuals regardless of their age, gender or socio-economic condition.(WHO) Depression is common, affecting about 121 million people worldwide it is one of the common cause of disability. (WHO, 2010) Methods :Cross-sectional descriptive study was done at Shikshadeep College and Greenland International College, Biratnagar to find prevalence and factor affecting depression. 438 samples was calculated using formula 4pq/d2 taking 5% as an error. A self-administered questionnaire was given to students to obtain information. The main analysis part was association between the age, sex and factors. Results: A total of 438 samples were recruited for the study. Among the samples recruited, 37% were female where 63% were male studying in higher secondary level. Among them 58% were depressed. Main factor for causing depression was personal relationship or problem. Discussion and Conclusion :This study provided the knowledge about the factors affecting depression among higher secondary level students. This study also told that maximum number of male where affected than that of female and main factor to cause depression was personal relationships or problems. Recommendation: This is small scale study so large scale study must be done to get good result and quantitative study may be helpful for the better results.